Learning organization: Team Learning in Achieving International Green Campus at UIN Raden Intan Lampung - Sada, Heru Juabdin (Universitas Islam Negeri Raden Intan Lampung, 2023)
This study aimed to investigate the team learning model at UIN Raden Intan Lampung as an international green campus. This study employed a qualitative approach, where the data was obtained from the heads of university and faculties. The data collection techniques utilized in this study included interviews, observations, documentation, and questionnaires. The study employed Nvivo 12Plus software for data analysis, which involved seven stages: open coding, axial coding, selective coding, matrix coding query, and word frequency query. The analysis of the learning organization research on team learning reveals that the leadership model is consistently evolving for the better, such as through interaction-expectation theory. For instance, the leaders of UIN Raden Intan Lampung excel at effectively communicating messages to ensure a shared understanding among team members, thus minimizing the risk of miscommunication. Building a strong work team is essential for fostering individual and group growth, enabling UIN Raden Intan leaders to manage conflicts effectively.